Indian data on central nervous tumors: A summary of published work - Dasgupta, Archya; Gupta, Tejpal; Jalali, Rakesh (South Asian Journal of Cancer, 2016)
Tumors of the central nervous system (CNS) constitute approximately 2% of all malignancies. Although relatively rare, the associated morbidity and mortality and the significant proportion of affected young and middle-aged individuals has a major bearing on the death-adjusted life years compared to other malignancies. CNS tumors encompass a very broad spectrum with regards to age, location, histology, and clinical outcomes. Advances in diagnostic imaging, surgical techniques, radiotherapy equipment, and generation of newer chemotherapeutic and targeted agents over the past few years have helped improving treatment outcome. Further insights into the molecular pathways leading to the development of tumors made in the past decade are being incorporated into routine clinical practice. Several focused groups within India have been working on a range of topics related to CNS tumors, and a significant body of work from India, in the recent years, is being increasingly recognized throughout the world. The present article summarizes key published work with particular emphasis on gliomas and medulloblastoma, the two commonly encountered tumors.
Keywords: Central nervous system tumor; glioma; Indian data; medulloblastoma